Mitochondrial Dysfunction in Cancer - Boland, Michelle L.; Chourasia, Aparajita H.; Macleod, Kay F. (Frontiers in Oncology, 2013)
A mechanistic understanding of how mitochondrial dysfunction contributes to cell growth and tumorigenesis is emerging beyond Warburg as an area of research that is under-explored in terms of its significance for clinical management of cancer. Work discussed in this review focuses less on the Warburg effect and more on mitochondria and how dysfunctional mitochondria modulate cell cycle, gene expression, metabolism, cell viability and other more conventional aspects of cell growth and stress responses. There is increasing evidence that key oncogenes and tumor suppressors modulate mitochondrial dynamics through important signaling pathways and that mitochondrial mass and function vary between tumors and individuals but the sigificance of these events for cancer are not fully appreciated. We explore the interplay between key molecules involved in mitochondrial fission and fusion and in apoptosis, as well as in mitophagy, biogenesis and spatial dynamics and consider how these distinct mechanisms are coordinated in response to physiological stresses such as hypoxia and nutrient deprivation. Importantly, we examine how deregulation of these processes in cancer has knockon effects for cell proliferation and growth. Scientifically, there is also scope for defining what mitochondria dysfunction is and here we address the extent to which the functional consequences of such dysfunction can be determined and exploited for cancer diagnosis and treatment.